Analisis Lingkungan Kerja Karyawan Pada Female Daily Network - Raihan Nurrohman; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Manajemen Riset Inovasi, 2024)
This research applies a qualitative descriptive method with the aim of describing and analyzing the issues found. This qualitative approach is based on collecting primary and secondary data. Primary data in this research was obtained through observation, interviews, and documentation, while secondary data was obtained through books, previous research, and articles relevant to this research. The data source in this research is interview transcripts obtained from a number of respondents called research informants. The informants were selected based on a certain method because their abilities or positions were deemed to be able to describe the problem that would be the object of research. The informants for this research were four people consisting of one head of the human resources division and three non-human resources division staff. The main objective of this research is to understand the employee work environment at the Female Daily Network company, including what factors influence the employee work environment and how the Female Daily Network creates a positive work environment. The results of this research show that respondents responded to the questions asked by researchers regarding the work environment. When interviewed by researchers, employees revealed that they noted differences in room arrangements at Female Daily Network, which also led to a lack of a sense of togetherness between various departments. This indirectly hinders social interaction and communication between employees from different departments within the company. This finding is strengthened by interview results which show that when problems arise in an unhealthy work environment, differences in room arrangements are one of the factors that play a role. The different room arrangements are carried out with the aim of limiting interference between divisions, so that employees can focus more on carrying out their duties.